Pengaruh Sistem Informasi Manajemen Sekolah (SIMS) dan Kompetensi Digital Tenaga Administrasi terhadap Efektivitas Administrasi Sekolah Menengah - Evi Purnawati; Sutrisni Andayani; M. Ihsan Dacholfany (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of School Management Information Systems (SIMS) and administrative staff competence in the digital era on the effectiveness of school administration in secondary schools. This research used a quantitative approach with a survey method. The population consisted of administrative staff in secondary schools, with 56 respondents selected using total sampling. Data were collected using a Likert scale questionnaire (1–4) consisting of 75 items: 25 items for SIMS (X1), 25 items for administrative competence (X2), and 25 items for administrative effectiveness (Y). Data analysis was conducted using validity tests, reliability tests (Cronbach’s Alpha), normality tests, multicollinearity tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results showed that administrative staff competence had a positive and significant effect on school administration effectiveness. Meanwhile, SIMS implementation did not have a significant partial effect. However, SIMS and administrative competence simultaneously had a significant effect on administrative effectiveness. This finding indicates that SIMS implementation will be effective only when supported by competent human resources.